2008
DOI: 10.1091/mbc.e07-08-0827
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein–induced Aggregation of Cytoplasmic Vesicles inSaccharomyces cerevisiae

Abstract: Aggregated ␣-synuclein (␣-syn) fibrils form Lewy bodies (LBs), the signature lesions of Parkinson's disease (PD) and related synucleinopathies, but the pathogenesis and neurodegenerative effects of LBs remain enigmatic. Recent studies have shown that when overexpressed in Saccharomyces cerevisiae, ␣-syn localizes to plasma membranes and forms cytoplasmic accumulations similar to human ␣-syn inclusions. However, the exact nature, composition, temporal evolution, and underlying mechanisms of yeast ␣-syn accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
170
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(183 citation statements)
references
References 59 publications
9
170
1
3
Order By: Relevance
“…In neurons these structures appeared as small structures, distributed especially along the neurites and at their terminal tips. These foci, attached to and rolling onto the inner face of the plasma membrane, especially near the sites of cellto-cell interaction, appear as transient but specific structures, quite different from the protein clusters close to the plasma membrane recently reported in yeast cells overexpressing ␣-synuclein-GFP (Soper et al, 2008).…”
Section: Discussioncontrasting
confidence: 56%
“…In neurons these structures appeared as small structures, distributed especially along the neurites and at their terminal tips. These foci, attached to and rolling onto the inner face of the plasma membrane, especially near the sites of cellto-cell interaction, appear as transient but specific structures, quite different from the protein clusters close to the plasma membrane recently reported in yeast cells overexpressing ␣-synuclein-GFP (Soper et al, 2008).…”
Section: Discussioncontrasting
confidence: 56%
“…Several Rab GTPases were suggested to interact aberrantly with αS in Dementia with Lewy bodies (Soper et al, 2008(Soper et al, , 2011Sung et al, 2001). In addition, Rab proteins colocalize with glial inclusions containing αS in multiple system atrophy (Dalfo and Ferrer, 2005;Nakamura et al, 2000), Rab GTPases were found in vesicle clusters induced by αS overexpression in yeast (Gitler et al, 2008), and overexpression of the Rab GTPases Rab1, Rab3a and Rab8a decreased αS-induced neurotoxicity (Cooper et al, 2006;Gitler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of -synuclein in yeast and mammalian cells causes delays in ER-to-Golgi vesicle trafficking, an effect that was more striking with the A53T mutant (Cooper et al, 2006;Thayanidhi et al, 2010). These changes in ER-to-Golgi trafficking by -synuclein may be caused by immobilizing vesicles in the cytoplasm (Soper et al, 2008). The mechanism appears to involve rab proteins, small GTPases that regulate vesicle trafficking, as the impairment is rescued by overexpressing certain rab proteins (Gitler et al, 2008).…”
Section: -Synuclein Outside Of Diseasementioning
confidence: 99%
“…From a functional perspective, -synuclein appears to antagonize rab3a function. For example, over-expression of -synuclein in yeast interfered with ER-to-Golgi vesicle trafficking that was corrected by the simultaneous over-expression of the yeast homologue of rab1 (Cooper et al, 2006;Soper et al, 2008). Similarly, elevated toxicity in nematodes and rat primary neurons engineered to express wild-type or A53T -synuclein was rescued by the addition of rab8 or rab3a (Gitler et al, 2008).…”
Section: Rab3amentioning
confidence: 99%
See 1 more Smart Citation